PENGARUH LUAS PENGUNGKAPAN SUKARELA TERHADAP HUBUNGAN ANTARA LABA DENGAN RETURN SAHAM DALAM LAPORAN TAHUNAN - Bagas Jati Nugroho; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2014)
This study aims to analyzes the effect of voluntary disclosure of a company listed on the Indonesia Stock Exchange (IDX) for the influence the association between earnings and current returns. Hypothesis alternative was used: (Ha) the higher level of voluntary disclosure improves the association between earnings and current returns. This study uses 48 companies listed on IDX 2009. Company annual reports audited as by a public accounting firm and published reports of the independent auditor. Companies publish the audited annual report as of December 31 and complete on 2010. The result of this study is that (Ha) the higher level of voluntary disclosure improves the association between earnings and current returns.